2021
DOI: 10.3390/molecules26185724
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Evaluation of Iranian Medicinal Plant Phytoconstituents as Inhibitors against Main Protease and the Receptor-Binding Domain of SARS-CoV-2

Abstract: The novel coronavirus disease 2019 (COVID-19) is caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which initially appeared in Wuhan, China, in December 2019. Elderly individuals and those with comorbid conditions may be more vulnerable to this disease. Consequently, several research laboratories continue to focus on developing drugs to treat this infection because this disease has developed into a global pandemic with an extremely limited number of specific treatments available. Natu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 98 publications
4
26
2
Order By: Relevance
“…Some of them are repurposed antiviral medications that have been approved by the Food and Drug Administration (FDA) [21,22]. Other initiatives include the search for drugs that are derived from medicinal plants [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Some of them are repurposed antiviral medications that have been approved by the Food and Drug Administration (FDA) [21,22]. Other initiatives include the search for drugs that are derived from medicinal plants [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…The toxicity analysis considered several parameters, including the LD 50 , predicted toxicity class, hepatotoxicity, carcinogenicity, immunotoxicity, mutagenicity, and cytotoxicity. Toxicity levels are classified as follows: classes 1 and 2 (fatal if swallowed), class 3 (toxic if swallowed), class 4 (harmful if swallowed), class 5 (possibly harmful if swallowed), and class 6 (nontoxic) [ 58 ]. The predicated LD 50 of the peptide is 500 mg/kg, which classified the molecule in class 4, indicating it is harmful if swallowed.…”
Section: Resultsmentioning
confidence: 99%
“…A lesser hydrogen bonding interaction and higher hydrophobic interaction signified that the latter have a greater contribution to the binding affinity and stability of a ligand in an enzyme’s binding pocket [ 25 ]. In this study, only one hydrogen bonding interaction was observed for arcommunol B, manuifolin H, and kuwanon F, while none was observed for kuwanon S. This indicated that hydrophobic interaction was more prevalent and contributed exceedingly to the binding affinity and stability of the ligands in the glucokinase enzyme’s binding pocket.…”
Section: Resultsmentioning
confidence: 99%